Pengaruh Kematangan Pegawai, Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Pegawai - Theodore, Fransisca Angelina; Silalahi, Gunawan; Depari, Mota; Meirini, Meirini; Hendhika, Hendhika; Safrida, Safrida; Helmi, T. Ahmad; Wasesa, Supar (Journal of Management and Economics Research, 2024)
This study aims to determine the effect of employee maturity, work environment and work stress partially and simultaneously on the performance of employees work in the Kantor Pelayanan Pajak Pratama Medan Barat. The study was conducted at the Kantor Pelayanan Pajak Pratama Medan Barat Jalan Asrama Nomor 7A Medan, with a population of 115 people, and a study sample. of 54 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24. Based on the analysis results obtained employee maturity has a effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Barat, this is supported by the results of t count analysis > t-table (3,324 > 2,009) at n = 54 at 95% significance level. Work environment has a effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Barat, this is supported by an analysis of t count > t-table (8,397 > 2,009) at n = 54 at 95% significance level. Work stress has a negatif effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Barat, this is supported by an analysis of t count < -table (3,821 < 2,009) at n = 54 with a significant level of 95%.Value of F-count > F table (62,584 > 2,79) This states that together (multiple) there are positive and significant effects of employee maturity, work environment and work stress on the performance of employees work of employees of the Kantor Pelayanan Pajak Pratama Medan Barat. Thus the hypothesis proposed is accepted by the truth.